Recent Publications (Quarterly Journal of Economics, 1943)
Recent Publications Get access The Quarterly Journal of Economics, Volume 57, Issue 3, May 1943, Pages 494–496, https://doi.org/10.1093/qje/57.3.494 Published: 01 May 1943